Teatre en català a València durant el franquisme: crisi d’un model escènic - Pérez i Moragón, Francesc (Caplletra. Revista Internacional de Filologia, 2015)
The performance of commercial drama in Catalan was resumed in Valencia in 1945, once the harshest moment of the post-war was over. But the genre did not recover the vivacious spirit it had presented Up to 1936. The process of linguistic replacement, the stagnation of writers’ aesthetic formulae, the change of habits in audiences and other factors practically resulted in its dissapearance off stage.